Regionale forskelle på udmøntning og møntbrug i Danmark ca. 1050 - ca. 1500 - Jensen, Jørgen Steen (Hikuin, 2008)
Regional differences in coinage and monetary circulation in Denmark c. 1050-c. 1500 By Jørgen Steen Jensen A system of regular mints was introduced into Denmark during the reign of Cnut (c. 1018-35). It is evident that the coins from Jutland were struck to a lighter standard (c. ¾ gram) than the coins in Eastern Denmark (Scania and Sealand) (c. 1 gram). The difference is upheld during most of the 11th century and well into the 12th century, culminating, so to say, with the small bracteates of Northern Jutland in the middle of the 12th century, weighing between a fifth and a quarter of a gram. In the 13th century there were several mints in the country, Scania, Sealand, Northern and Southern Jutland, but in the middle of the century there is a growing tendency to strike better coins at the mint of Lund than in the rest of the country. This is expressed in the strife between the archbishop of Lund and the king in 1298. The archbishop expresses his wish to have the Scanian denars struck to the same standard as the denier tournois. The archbishop was apparently successful in his argumentation, and the Lund coinage would seem to have been struck to this standard till the mint was closed in the 1370s, the other Danish mints striking a very debased coinage until they were closed after the death of King Christoffer II in 1332. In the early 15th century Danish mints were established again, but the minting of the widespread copper sterlings c. 1420-c.1430/35 took place at four mints, one in each major province, Scania, Sealand, Funen and Jutland (Lund, Næstved, Odense and Randers). Apparently it is only a question of logistics which makes the establishing of the four mints important, as there is nothing to indicate any regional differences in the standard or fineness. In most of the 2nd half of the 15th century only one mint existed, that of Malmø, but late in the century mints were established both in Copenhagen and Aalborg. Here again it rather seems to be a question of rational distribution.